A Learning Module for the Approach to Pediatric Urologic Emergencies - Mark Assmus; Peter Metcalfe (Association of American Medical Colleges, 2014)
Abstract This resource provides an overview of eight key pediatric urologic emergencies, including testicular torsion, paraphimosis, disorders of sexual differentiation, nephrolithiasis, antenatal hydronephrosis, incarcerated inguinal hernia, hydroceles, and major abdominal birth defects. It is part of the PedsCases series. The goal of PedsCases is to develop a comprehensive educational tool that focuses on the core objectives of undergraduate pediatric education. This teaching module includes Word documents, interactive cases with questions, and a podcast. In the podcast, each condition is documented with a brief description of presenting signs and symptoms, key differential diagnoses, and an approach to the proper diagnostic workup and appropriate therapeutic management. Additionally, two case presentations are provided with supplemental multiple-choice questions to further enhance an evidence-based approach to understanding pediatric urologic emergencies. PedsCases has been integrated into the third-year undergraduate pediatric medical education curriculum at the University of Alberta. The series is one of the main sources recommended to students to cover the core objectives of the clinical pediatric rotation and to assist in preparing for the final examinations. Since the focus of medical education has shifted towards independent learning, PedsCases has become an essential tool.